Cooperative Robots and Sensor Networks 2015 - Koubâa, Anis; Martínez-de Dios, J.Ramiro (Studies in Computational Intelligence,, 2015)
This book compiles some of the latest research in cooperation between robots and sensor networks. Structured in twelve chapters, this book addresses fundamental, theoretical, implementation and experimentation issues. The chapters are organized into four parts namely multi-robots systems, data fusion and localization, security and dependability, and mobility.